Construction and validation of a booklet for parents/caregivers of children with attention deficit and hyperactivity disorder - Silva, Kely Vanessa Leite Gomes da; Rebouças, Cristiana Brasil de Almeida; Neto, João Cruz; Almeida, Paulo César de (Revista Cuidarte, 2023)
Introduction: Educational materials, such as booklets, are tools that help in caregiving and elucidate relevant and sensitive interventions to the health context, especially in home care for children with neurodevelopmental disorders. Objective: to build and validate a booklet to guide parents and caregivers of children with attention deficit hyperactivity disorder. Materials and Methods: methodological study for the construction and validation of a booklet by judges and the target audience. The material was written, designed, and laid out with subsequent validation by judges, considering the content validity index for data analysis. Results: booklet composed of 13 themes and 32 pages. The validation had 21 content judges obtaining an index of 0.89. Seven judges in appearance evaluated and scored the index of 0.91. 17 participants from the target audience evaluated general content with an index of 0.99. After adjustments, the readability index obtained a satisfactory percentage of 54%. Discussion and Conclusion: The constructed material portrays the daily life of families, presents illustrations in health and education services and is sensitive to the studied audience. The booklet was considered valid in terms of content and appearance and suitable for use in nursing care for children with the disorder, contributing to adequate guidance for parents and caregivers.How to cite this article: Silva, Kely Vanessa Leite Gomes; Rebouças, Cristiana Brasil de Almeida; Cruz Neto, João; Almeida, Paulo Cesar. Construção e validação de cartilha para pais/cuidadores de crianças com déficit de atenção e hiperatividade. Revista Cuidarte. 2023;14(3):e3037. http://dx.doi.org/10.15649/cuidarte.3037
Keywords: ttention Deficit Disorder with Hyperactivity; Educational Technology; Validation Study; Health Education; Nursing